A comparative population‐based analysis of sinonasal diffuse large B‐cell and extranodal NK/T‐cell lymphomas. (27th December 2014) - Dubal, Pariket M.; Dutta, Rahul; Vazquez, Alejandro; Patel, Tapan D.; Baredes, Soly; Eloy, Jean Anderson
<x xml:space="preserve">Abstract</x> Objective/Hypothesis Diffuse large B‐cell lymphoma (DLBCL) and extranodal natural killer/T‐cell lymphoma (ENKTL) are aggressive tumors. ENTKL is very rare in the United States and often affects the nasal cavity and paranasal sinuses; DLBCL, although more common, rarely occurs in these locations. Our study aims to compare incidence and survival of these lymphomas in the sinonasal cavity. Study Design Retrospective analysis of the United States National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) registry. Methods The SEER database was searched for patients diagnosed with sinonasal ENKTL and DLBCL between 1973 and 2011. Data analyzed included patient demographics, incidence, treatment modality, and survival. Results Three hundred and twenty‐eight sinonasal ENKTL (SN‐ENKTL) cases and 1, 054 sinonasal DLBCL (SN‐DLBCL) cases were identified. The mean ages at diagnosis for SN‐ENKTL and SN‐DLBCL were 51.7 and 67.8 years, respectively (P = 0.0001). Overall 1‐, 5‐, and 10‐year disease‐specific survival (DSS) rates for SN‐DLBCL were 85.5%, 63.5%, and 44.0%, compared to 66.4%, 30.9%, and 9.2% for SN‐ENKTL, respectively (P < 0.0001). For patients matched for stage, age, and treatment modality, the 1‐, 5‐, and 10‐year DSS for the SN‐DLBCL group was 94.4%, 72.8%, and 46.8%, respectively, whereas the respective survival rates for the SN‐ENKTL group were 77.6%, 38.4%, and 13.9%, respectively (P < 0.0001 at each time interval). Conclusions To our knowledge, this study represents the only population‐based comparison between SN‐DLBCL and SN‐ENKTL. SN‐DLBCL has a better prognosis regardless of gender, stage, treatment modality, and age. Level of Evidence 2b. Laryngoscope, 125:1077–1083, 2015